Dosing Recommendations for Quetiapine When Coadministered With HIV Protease Inhibitors. (19th November 2018) - Sampson, Mario R.; Cao, Kelly Y.; Gish, Paula L.; Hyon, Kyong; Mishra, Poonam; Tauber, William; Zhao, Ping; Zhou, Esther H.; Younis, Islam R.
Abstract: Although current quetiapine labeling recommends that its dosage should be lowered 6‐fold when coadministered with strong cytochrome P450 (CYP)3A inhibitors, a reported case of coma in a patient receiving quetiapine with lopinavir and ritonavir prompted the reevaluation of labeling recommendations for the dosing of quetiapine when coadministered with human immunodeficiency virus (HIV) protease inhibitors. Literature and database (FDA Adverse Event Reporting System and United States Symphony Health Solutions' Integrated Dataverse Database) searches allowed us to identify cases of coma and related adverse events involving the coadministration of quetiapine and HIV protease inhibitors and to estimate the frequency of concomitant use. Literature review and physiologically based pharmacokinetic modeling allowed us to estimate the potential for CYP3A inhibition to contribute to adverse events related to HIV protease inhibitor–quetiapine coadministration. We identified excess sedation following coadministration of quetiapine and an HIV protease inhibitor in 3 reports without obvious confounders. In prescription claims data, 0.4% of quetiapine patients were dispensed a concurrent ritonavir prescription. The quetiapine dose was not reduced on ritonavir initiation in 90% of therapy episodes. Available data indicate to us that all HIV protease inhibitors combined with ritonavir are likely to be strong CYP3A inhibitors. We predicted that ritonavir would increase quetiapine exposure comparable to the strong CYP3A inhibitor ketoconazole. The current dosing recommendations for use of quetiapine with strong CYP3A inhibitors (ie, 6‐fold lower quetiapine dose) are appropriate and should be followed when quetiapine is coadministered with HIV protease inhibitors.